Foreign Private Investment Flows and Manufacturing Sector in Zimbabwe - Chinodzama, Delia (Graduate School of Business (GSB), 2022)
The study primarily examined the macroeconomic and institutional factors constraining the flow of foreign private investment flows into Zimbabwe's manufacturing sector. The study further explored the benefits that accrue from private capital as a source of financing for Zimbabwe's manufacturing sector. Quantitative analysis was used to determine the macroeconomic and governance factors that have a significant impact on the flow on private capital into Zimbabwe. Using the Johansen cointegration trace and maximum eingen value test indicate the presence of a significant long-run relationship between foreign capital inflows and the predictor variables. The results indicated the presence of 5 integrating equations for the trace test and 3 cointegrating equations for the maximum eingen value test. The normalized coefficients, foreign private investment flows are significantly and positively impacted by infrastructure development, economic growth rate, and inflation (macroeconomic factors) and further by business freedom and government effectiveness (governance factors). GDP per capita was found to have a negative impact on foreign investment flows. Analysis of questionnaire data revealed that foreign private financing appeals highly to manufacturing companies but access to this source of funding is constrained by funding mismatches, high credit risk levels within the local manufacturing industry, a longer time lag, sanctions imposed on the country and high production costs. In terms of the benefits of foreign private capital over the traditional sources of funding, the study found that private capital improves company operations (capacity utilisation, export market penetration and productivity), improves technology usage, and boosts the target company's corporate image.